2022
DOI: 10.3389/fmed.2022.879210
|View full text |Cite
|
Sign up to set email alerts
|

Classification-Based Approaches to Myopia Control in a Taiwanese Cohort

Abstract: PurposeMyopia is a disorder of growing prevalence in school-aged children worldwide, especially in Asia. Although low-dose atropine is recognized as an effective treatment to slow myopia progression, different studies have reported varying efficacies of treatment, and the optimal concentration of low-dose atropine remains an open question.MethodsA two-stage approach was conducted in this study. First, an observational study was conducted to plot the axial length growth curve for Taiwanese children. Second, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…After screening by title and abstract, 171 articles were selected for full‐text view. Finally, 31 studies were identified that fulfilled the eligibility criteria 12–42 . The study flow was depicted according to the PRISMA guidelines in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, 171 articles were selected for full‐text view. Finally, 31 studies were identified that fulfilled the eligibility criteria 12–42 . The study flow was depicted according to the PRISMA guidelines in Figure 1.…”
Section: Resultsmentioning
confidence: 99%